Sympathy for the Devil? Uncovering Inhibitors and Enablers of Emotional Engagement Between Zoo Visitors and the Tasmanian Devil, Sarcophilus harrisi. Issue 1 (2nd January 2019) - Markwell, Kevin; Weiler, Betty; Skibins, Jeffrey C.; Saunders, Robert
Abstract: This article explores enablers and inhibitors of emotional engagement between visitors and Tasmanian devils at Healesville Sanctuary, Australia. A qualitative research approach was utilized including 44 interviews (ten with staff and 34 with visitors) and eight hours of observations of 622 visitors. Findings are presented in relation to six themes: (a) visitors' motivations for viewing Tasmanian devils, (b) visitors' emotional responses to Tasmanian devils, (c) role of previsit expectations, (d) species' attributes inhibiting emotional engagement, (e) species' attributes enabling emotional engagement, and (f) elements of exhibit design and interpretation influencing emotional engagement. Results show clear views of active animals, first-person interpretation, and an understanding of conservation threats were enablers of forming an emotional connection. Inability to view animals and general misconceptions of devils were inhibitors of forming an emotional connection. Implications for exhibit management, interpretation, and conservation are discussed.